Human reasources policy manual - Arahood, Dale A.; Bank Administration Institute (Bank Administration Institute : Rolling Meadows, Illinois, 1988)
The manual is directed to managers and supervisors. It discusses significant human resources procedures, as well as sample policies, and identifies supervisory duties and responsibilities in relation to the bank, to subordinates, and to other supervisors. The book provides the foundation for practices and procedures.
Includes bibliographical references p. 173-174 and index.
hza 24/07/2018
Loan
Keywords: Human resources; United States